2017
DOI: 10.1002/slct.201700053
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Substituted Cucurbit[6]uril Assisted Competitive Fluorescence Recognition of Lysine and Methionine in Aqueous Solution

Abstract: The use of competitive ratiometric fluorescence indicator displacement chemosensors derived from two alkyl substituted cucurbit[6]uril‐based host‐guest complexes is reported. In particular, the differing binding abilities of two cucurbit[6]uril derivatives towards the target analytes led to a useful ratiometric detection signal output for the discrimination of lysine and methionine versus the other tested α‐amino acids in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…CB s can selectively accommodate and interact with amino acids and small peptides in water (Bush et al, 2005; Urbach and Ramalingam, 2011; Gamal-Eldin and Macartney, 2013; Biedermann and Nau, 2014; Lee et al, 2015; Smith et al, 2015; Kovalenko et al, 2016; Bai et al, 2017). The binding of amino acids and their corresponding decarboxylated adducts to CB7 was explored by Bailey et al The study revealed a higher affinity for the decarboxylated molecules (Bailey et al, 2008).…”
Section: Encapsulation Of Drugsmentioning
confidence: 99%
“…CB s can selectively accommodate and interact with amino acids and small peptides in water (Bush et al, 2005; Urbach and Ramalingam, 2011; Gamal-Eldin and Macartney, 2013; Biedermann and Nau, 2014; Lee et al, 2015; Smith et al, 2015; Kovalenko et al, 2016; Bai et al, 2017). The binding of amino acids and their corresponding decarboxylated adducts to CB7 was explored by Bailey et al The study revealed a higher affinity for the decarboxylated molecules (Bailey et al, 2008).…”
Section: Encapsulation Of Drugsmentioning
confidence: 99%
“…Their varied chemistry and structures together with potential applications have been discussed in a number of recent reviews. We and others have been interested in their host–guest chemistry, as well as the application of their recognition properties [ 2 , 3 , 4 , 5 , 6 ]. We have also been attracted by a number of reports in which a smaller member of the Q[ n ] family can be trapped in the cavity of a larger member of the series.…”
Section: Introductionmentioning
confidence: 99%
“…Gas uptake by CB6 and displacement of the indicator dye was in this example coupled to a significant reduction (factor > 2) in the emission intensity. [186] This chemosensing ensemble responded selectively to the presence of methionine (Met) and lysine (Lys) whereas the other proteinogenic amino acid did not give a significant fluorescence change. [22] A chromophoric and fluorescent aminonaphthalimide-putrescine conjugate was reported by the Pischel group that enabled the detection of biogenic amines under physiological pH conditions.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Isaacs and co-workers have successfully employed this indicator dye to monitor gas uptake by acyclic CBn derivatives. [186,235] This feature can be of practical relevance when setting up differential sensing arrays. [234] A ratiometric IDA was established by Ni, Tao and co-workers using the selfaggregating bispyridinium phenylene-vinylene (PPV) dye (aggregation occurs in the presence of nitrate salts) whose emission colour is hypsochromic shifted by 120 nm upon addition of the partially methyl-substituted CB6 derivatives, Me 4 CB6 and Me 6 CB6 (see Figure 2a for their chemical structures).…”
Section: Mass Spectrometrymentioning
confidence: 99%